Analysis Of Work Posture On Musculoskeletal Disorders (Msds): Literature Review - Hasna Nabilla Noor Salma (International Journal of Health Engineering and Technology, 2026)
Musculoskeletal Disorders (MSDs) are one of the most common work-related health problems and a major cause of reduced productivity and disability among workers in various industrial sectors. One of the main risk factors for MSDs is non-ergonomic work postures, such as bending, sitting or standing statically for long periods of time, repetitive movements, and excessive use of force that exceeds the body's physiological capacity. This literature review aims to analyze the relationship between work posture and Musculoskeletal Disorders (MSDs) complaints based on research results published in accredited scientific journals from 2021 to 2024. The method used was a literature review of articles that assessed work posture using ergonomic instruments such as the Rapid Entire Body Assessment (REBA), Rapid Upper Limb Assessment (RULA), Nordic Body Map (NBM), and PLIBEL Checklist. The results of the study show that most studies found a significant relationship between non-ergonomic work posture and increased MSD complaints, especially in the neck, shoulders, lower back, waist, and wrists. In addition to work posture, age and length of service also contribute to an increased risk of musculoskeletal complaints. Thus, improving work design and applying ergonomic principles are important steps in preventing and controlling MSDs in the workplace.